2020
DOI: 10.3390/ma13245785
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Embrittlement at Cleavage Planes and Grain Boundaries in Bcc Iron—Revisiting the First-Principles Cohesive Zone Model

Abstract: Hydrogen embrittlement, which severely affects structural materials such as steel, comprises several mechanisms at the atomic level. One of them is hydrogen enhanced decohesion (HEDE), the phenomenon of H accumulation between cleavage planes, where it reduces the interplanar cohesion. Grain boundaries are expected to play a significant role for HEDE, since they act as trapping sites for hydrogen. To elucidate this mechanism, we present the results of first-principles studies of the H effect on the cohesive str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Previously, related research showed that the mechanistic characteristics of hydrogen-assisted fracture transformed from dimples ductile fracture (microvoid coalescence (MVC)) without hydrogen to brittle fracture (quasi-cleavage (QC) or intergranular (IG) fracture + transgranular (TG) fracture mechanism) under hydrogen-charged condition [4,5]. For the HE mechanism, some classical theories have been developed, and so far the following three theories have been widely accepted: a hydrogen-enhanced decohesion (HEDE) mechanism [6][7][8][9], in which it is assumed that hydrogen atoms entering the steel causes lattice expansion and reduces surface energy. The second theory is a hydrogenenhanced localized plasticity (HELP) mechanism [10][11][12][13], which states that hydrogen atoms in steel enhance dislocation mobility, thus reducing apparent yield stress and promoting local plastic deformation under low stress or stress intensity factor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, related research showed that the mechanistic characteristics of hydrogen-assisted fracture transformed from dimples ductile fracture (microvoid coalescence (MVC)) without hydrogen to brittle fracture (quasi-cleavage (QC) or intergranular (IG) fracture + transgranular (TG) fracture mechanism) under hydrogen-charged condition [4,5]. For the HE mechanism, some classical theories have been developed, and so far the following three theories have been widely accepted: a hydrogen-enhanced decohesion (HEDE) mechanism [6][7][8][9], in which it is assumed that hydrogen atoms entering the steel causes lattice expansion and reduces surface energy. The second theory is a hydrogenenhanced localized plasticity (HELP) mechanism [10][11][12][13], which states that hydrogen atoms in steel enhance dislocation mobility, thus reducing apparent yield stress and promoting local plastic deformation under low stress or stress intensity factor.…”
Section: Introductionmentioning
confidence: 99%
“…The second theory is a hydrogenenhanced localized plasticity (HELP) mechanism [10][11][12][13], which states that hydrogen atoms in steel enhance dislocation mobility, thus reducing apparent yield stress and promoting local plastic deformation under low stress or stress intensity factor. The third theory is an adsorption-induced dislocation emission (AIDE) mechanism [9][10][11][12][13][14], and it is assumed that hydrogen atoms promote dislocation emission and motion to reach critical conditions, and hydrogen-induced crack nucleation causes damage. Apparently, out of these three theories, no single theory can provide adequate explanation of the HE mechanism, thus it seems that different mechanical systems correspond to different theories [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…This discrepancy is likely due to the fact that atomic relaxations were allowed in [22], while they were prevented for the validation herein -both for the DFT and classical modelling. In fact, for iron and nickel GBs it has been found that rigid and relaxed GB separation modelling can give contradictory results and that atomic relaxation is necessary to quantitatively capture the impact of impurities on the GB strength [52,78]. Nevertheless, as for the previously mentioned cases, the peak stresses for impurity inhabited GBs are within 10% of those predicted by DFT, suggesting good predictability.…”
Section: Traction-separation Properties and Generalized Stacking Faul...mentioning
confidence: 89%
“…Last but not least, the ORGS model 48 corresponds to the RGS with subsequent atomistic relaxation, which is named RGS + relaxation or RGSrel in many studies. 28,47,62,63 Following a comprehensive comparison of the various tensile testing methods outlined in the literature, 27,28,48,55,59,61,63 the RGS and RGSrel methods were performed for the GB structure in the current work. The key performance of the RGS approach requires that the investigated GB/bulk region should be split into two free surfaces by inserting an increasing separation distance.…”
Section: Computational Detailsmentioning
confidence: 99%